Constraints based scheduling in the multi-project environment - Skołud, Bożena; Zientek, Aleksandra (Computer Assisted Methods in Engineering and Science, 2005)
The paper deals with the problem of new projects acceptance into the multi project environment, where constraints are limiting the number of projects that a company is able to carry out concurrently. The objective of this paper is to answer the question: Is it possible to execute new project on time in the multiproject environment? For answering the question combination of Theory of Constraints and conditions guaranteeing project due dates with constraint-based scheduling are proposed. As a result the decision of the project implementation and the schedule of project activities, which the company is able to implement concurrently are obtained.